Magnetic reconnection driven by intense lasers. (31st August 2018) - Zhong, Jiayong; Yuan, Xiaoxia; Han, Bo; Sun, Wei; Ping, Yongli
Abstract : Laser-driven magnetic reconnection (LDMR) occurring with self-generated B fields has been experimentally and theoretically studied extensively, where strong B fields of more than megagauss are spontaneously generated in high-power laser–plasma interactions, which are located on the target surface and produced by non-parallel temperature and density gradients of expanding plasmas. For properties of the short-lived and strong B fields in laser plasmas, LDMR opened up a new territory in a parameter regime that has never been exploited before. Here we review the recent results of LDMR taking place in both high and low plasma beta environments. We aim to understand the basic physics processes of magnetic reconnection, such as particle accelerations, scale of the diffusion region, and guide field effects. Some applications of experimental results are also given especially for space and solar plasmas.